Trace nickel determination in seawater matrix using combination of dispersive liquid-liquid microextraction and triethylamine-assisted Mg(OH)2 method - Kublay, Irem Zehra; Kocoglu, Elif Seda; Oflu, Sude; Arvas, Busra; Yolacan, Cigdem; Bakirdere, Sezgin (SPRINGER, 2023)
In order to eliminate the effects of seawater matrix on the precise/accurate determination of elements, new and efficient analytical procedure requires. In this study, co-precipitation method based on the triethylamine (TEA)-assisted Mg(OH)(2) was performed to eliminate side-effects of seawater medium on the determination with flame atomic absorption spectrometry (FAAS) prior to the preconcentration of nickel by an optimized dispersive liquid-liquid microextraction (DLLME) method. Under the optimum conditions of the presented method, the limit of detection and quantification (LOD, LOQ) values obtained for nickel were found as 16.1 and 53.8 & mu;g kg(-1), respectively. Seawater samples collected from West Antarctic region were used for real sample applications to check the accuracy and applicability of developed method, and satisfying recovery results (86-97%) were obtained. In addition to this, the digital image-based colorimetric detection system and the UV-Vis system were applied to confirm the applicability of the developed DLLME-FAAS method in other analytical systems.
Keywords: DLLME; FAAS; Nickel; Mg(OH)(2); TEA; Seawater; PLASMA-MASS SPECTROMETRY; ATOMIC-ABSORPTION-SPECTROMETRY; SOLID-PHASE EXTRACTION; IONIC LIQUIDS; PRECONCENTRATION; ELEMENTS; WATER; COPRECIPITATION; INJECTION; CHELATE; Environmental Sciences & Ecology